Vocabulary Acquisition Patterns in Adult Tertiary (ESL) Learners - Giridharan, Beena (Lambert Academic Publishing, 2013)
This study investigates patterns of second language (L2) learners’ vocabulary acquisition of English in pedagogical contexts, and develops a vocabulary acquisition model, specifically a pre-receptive to productive vocabulary (PR-PV) model which analyses the patterns of inferencing strategies, the role of context on the strategies, and the influence of teaching explicit strategies on vocabulary development. Research in the area of vocabulary development is unclear on the interrelationships among various aspects of lexical competence, learning, and production processes in second language lexical acquisition. Models of vocabulary acquisition in English as a second language are scarce and the lack often prompts L2 researchers to draw from first language vocabulary study models to correlate vocabulary developmental patterns. Research is also uncertain about how L2 learners respond to reading texts however, it is quite clear that the receptive vocabulary of L2 learners is larger than productive vocabulary.The study employed a mixed-method research approach and the findings suggest that both content and context play significant roles in the extent to which L2 learners interactefficiently with reading texts. The findings from the study may have pedagogical andtheoretical implications for curriculum developers, instructors and policy makers in second language tertiary English learning contexts.